The Effects of Solidification on the Microstructure and Mechanical Properties of Modified Ductile Ni-Resist Iron with a High Manganese Content - Mohd Rashidi, Maarof; Mohd Hasbullah, Idris (Elsevier, 2014)
In this study, ductile Ni-resist with a minimum nickel content of 18 wt% was modified. Up to 12 wt% manganese was added together with 10 wt% nickel to investigate the effects of the alloying elements on the solidification, microstructure and mechanical properties of the Ni-resist. The effects of the solidification stage on the primary dendrite arm spacing (DAS), secondary dendrite arm spacing (SDAS), graphite aggregates, carbide formation and a series of mechanical properties were evaluated. The results indicate that the DAS, SDAS, graphite aggregate and carbide are directly dependent on the solidification cooling rate. Consequently, various mechanical properties of the Ni-resist are also affected by the addition of manganese. The tensile strength of the modified ductile Ni-resist decreased as the manganese content increased.